The Competitive Effects of Declining Entry Costs over Time: Evidence from the Static Random Access Memory Market - An-Hsiang Liu; Ralph Siebert (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We focus on the estimation of market entry costs that are declining over time and evaluate their impact on competition and market performance. We employ a dynamic oligopoly model in which firms make entry, exit, and production decisions in the presence of declining entry costs and learning by doing effects. Focusing on the static random access memory industry, we show that entry costs drastically decline by more than 80 percent throughout the life cycle. This corresponds to entry cost reductions of 30 million per quarter. To show the relevance of declining entry cost, we perform three counterfactuals in which a social planner can (a) regulate entry, (b) charge a tax on entry, and (c) provide a subsidy to promote entry. Our simulations show that declining entry costs can lead to excessive entry costs that result from too early entries by firms. Tax and entry regulation policy can reduce the excessive entry problem having a positive effect on total surplus while reducing consumer welfare. In contrast, a subsidy policy intensifies the problem of excessive entry at early periods but it increases consumer welfare.
Keywords: C10; L10; L60; O30; 330; dynamic efficiency gains; entry costs; entry protection; entry regulation; market entry; market structure; semiconductor industry; social planner; subsidies; taxes